On the use of a programmable front-end for multi-band/multi-standard applications. (March 2016) - Abdelsalam, Hoda; Hegazi, Emad; Mostafa, Hassan; Ismail, Yehea
Abstract: Modern wireless devices require a compact wireless receiver that can access all the available services with fewer bulky off-chip passive components. This advocates the need for multi-band multi-standard receivers. This paper proposes a reconfigurable such receiver front-end controlled by its driving clocks. The receiver adopts charge sampling and impedance translation techniques. Its driving clocks are adjusted based on the targeted frequency. The receiver is tested over the existing standards specifications: GSM 2G (850 MHz, 900 MHz, 1.8 GHz and 1.9 GHz), UMTS 3G (850 MHz, 1.8 GHz, 1.9 GHz and 2.1 GHz), Bluetooth (2.4 GHz) and LTE (700 MHz→5 GHz) and Wi-Fi (2.4 GHz and 5 GHz). The proposed front-end architecture achieves NF of 8 dB, out-of-band IIP3 of 0 dBm and in-band IIP3 of −5 dBm across the tested frequencies in 65 nm CMOS technology. The design occupies 0.45 mm 2 .